USING HOT POTATOES PROGRAM FOR READING TEST INSTRUMENT IN ENGLISH TEACHING LEARNING PROCESS - Syamsudin Syamsudin; Lusy Kurniawati (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
In teaching learning process a test is used to examine students’ knowledge of something to determine what they know or have learned. Testing measures the level of skill or knowledge that has been reached. Most teachers still used paper based test in giving a test and it is not interactive anymore now. This study will deal with one interactive test items using hot potato program. It is a software program that can give teachers alternative in creating test items. It consists of five test forms; J-Quiz, J-Match, J-Cross, J-Cloze, and J-Mix. J-Quiz consists of four basic question types: multiple choice questions, short answer questions, hybrid question and multi select questions. J-Match can give matching questions or ordering exercises. J-Cross can give question in the form of crossword exercises. This can be used for vocabulary test. J-Cloze can perform cloze test items. And the last, J-Mix can perform the mix between J-Quiz and J-Match. This program actually can be applied into four skills; listening, speaking, reading, and writing. Hopefully, this paper only focuses on reading skill. By using hot potatoes in creating material for reading test, the students will feel enjoyable in doing the test. They will have a high spirit in learning English because it is a new challenge and experience for them.